SHALL I BECOME A PUBLIC ACCOUNTANT? - Webster, Norman E. (The Accounting Review, 1939)
Abstract The first question an accounting student should put to himself or herself, is, why he is thinking of preparing for and of engaging in the practice of public accountancy? Not many years ago some may have decided upon public accountancy because of the idea that its rewards in money were above the average, in some cases quite exceptional. But a professional life is not the most promising occupation to one imbued with the ambition of acquiring great wealth. There are notable exceptions in law and medicine, and some other professions. In accountancy fewer than 25,000 certificates have been issued. Probably there are less than 20,000 certified public accountants (CPAs) in practice and perhaps two or three times as many who are not certified. The number of those who have accumulated what could be considered as even approximating wealth is very few. Others may have thought of accounting as offering opportunities for reaching positions of distinction in the community. In politics, at least one CPA has gone to U.S. Congress and several have reached the legislatures. Perhaps there have been instances of accountants being elected or appointed to other important governmental positions. But for the positions for which accountants would seem to be especially fitted, the treasureships, the auditorships and the heads of departments of taxation, banking, insurance and the like, the selections of accountants have been very infrequent.